PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU SMK NEGERI 3 LAHAT - RAMADO ANUAR (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2024)
This study aims to analyze the effect of job satisfaction and organizational commitment on teacher performance at SMK Negeri 3 Lahat, South Sumatra. The study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to teachers and analyzed using multiple linear regression. The results indicate that job satisfaction has a positive and significant effect on teacher performance. Organizational commitment also shows a positive and significant effect on teacher performance. Simultaneously, job satisfaction and organizational commitment play an important role in improving teacher performance. These findings highlight the importance of managing psychological and organizational aspects to enhance teacher performance in vocational education institutions.